Deternation of Ethamsylate in PharmaceuticalPreparations by Liquid Chromatography - Nageswara Rao, R.; Nagaraju, P.; Sumanth Reddy, V.; Radha Krishnamurthy, P.; Uday Bhaskar, S.; Gopal, P. (Asian Journal of Chemistry, 2010)
Department of Pharmaceutical Chestry, College of Pharmaceutical Sciences,Berhampur, AT/PO-Mohuda Ganjam-760 002, India A reverse phase high-pressure liquid hromatographic method (HPLC) has been developed for the estimation of ethamsylate in its tablet dosage forms using RP- C18 column. The mobile phase (methanol, acetonitrile and phosphate buffer pH 2.8) was pumped at a flow rate of 1 mL /n in the ratio of 20 : 70 : 10 and the eluents were monitored at 290 nm. The intra- and inter-day variation was found to be less than 2% showing high precision of the assay method. The mean recovery of the drug from the solution containing 20 or 40 μg/mL was 98.72 ± 1.20% indicating high accuracy of the proposed HPLC method. Due to its simplicity, rapidness, high precision and accuracy, the proposed HPLC method may be used for deterning ethamsylate in bulk drug samples or in pharmaceutical dosage forms.